Prenatal Diagnosis of Unbalanced Translocation t(5;11)(q21;q22) With a Jacobsen Syndrome Clinical Phenotype - Yuri Hasegawa; Yuriko Kitajima; Koh Nagata; Shoko Miura; Kiyonori Miura (Clinical Case Reports)
ABSTRACT This case report describes a fetus with a Jacobsen syndrome phenotype, caused by an unbalanced translocation t(5;11)(q21;q22) resulting from an inherited balanced translocation from one of the parents; it underscores the importance of undertaking prenatal diagnosis and genetic counseling in parents to help plan for future pregnancies.